Should Medications Be Prescribed to Patients in Generic Form? Dental Practitioners’ Perspective - Saudamini G More; Tejal Patil; Tanvi Shetty; Monika Bhanushali; Hitesh Sawant (Journal of Indian Association of Public Health Dentistry)
Background: The initial line of dental treatment is antibiotic and analgesic prescription in order to control the inflammatory symptoms which add to the rising cost of dental care. The National Medical Commission mandates physicians to prescribe all drugs in their generic form. Objective: To harness the knowledge, attitude, and practice model to assess the cognizance of dental practitioners about generic medicines for dental patients and Pradhan Mantri Bhartiya Janaushadhi Pariyojana (PMBJP) by the Government of India. Methods: An electronic survey was done among 249 dental practitioners of Mumbai and Navi Mumbai region. A custom-made 25-item (close- and open-ended questions) questionnaire tool was used after validation from 10 subject matter experts. The questions asked were related to demography, knowledge, awareness, and preference of generic drugs. Results: Only 26.5% of the practitioners had adequate knowledge about generic drugs. Practitioners working in private setup and dental hospitals (P = 0.013) and those with lesser years of experience had adequate knowledge about generic drugs (P = 0.00). About 60% of practitioners were aware about the PMBJP scheme. Around 62% of participants were not confident about prescribing drugs in their generic form. Conclusion: Although most of the practitioners were aware of the PMBJP scheme, they lacked the awareness regarding generic drugs per se. Dental practitioners need to be updated in their knowledge of generic drugs to facilitate astute generic drug prescription.